The Effect of Resistance Training on Some Genes Related to Insulin Secretion in the Pancreas of Type 2 Diabetic Rats - Eizadi, Mojtaba; Ghofrani, Mohammad Hossein; Farazandeh, Mahdi (Shahroud Journal of Medical Sciences, 2024)
Background: Recently, the role of genetic components in the synthesis and secretion of insulin from the pancreatic islet cell has been raised many times. The present study was conducted with the aim of determining the effect of resistance training on serum insulin with emphasis on changes in TCF7L2 and GLUT2 expression in pancreas tissue in type 2 diabetic "T2D" rats. Methods: For this purpose, T2D was induced by intraperitoneal injection of nicotinamide and streptozotocin to 14 male Wistar rats and divided into exercise and control groups.Resistance training lasted 10 weeks 5 times/weekly for the exercise groups.After resistance intervention TCF7L2 and GLUT2 genes expression in pancreatic tissue, serum insulin, beta cell function and fasting were compared between groups by independent t test. Results: Compared to the control group, resistance training resulted in significant decrease in TCF7L2 expression "p = 0.006" and increase in GLUT2 expression "p = 0.016". In addition, significant decrease in glucose "p = 0.001" and increase in serum insulin "p = 0.002" as well beta cell function "p = 0.001" in exercise group was observed than the control group. Conclusion: Based on these findings, the improvement of glucose and serum insulin may be attributed to the increase and decrease of GLUT2 and TCF7L2 expression in pancreatic tissue in response to resistance training.